2005
DOI: 10.1042/bj20041891
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of PDX-1, MafA and E47/β2 to the regulation of the human insulin promoter

Abstract: The insulin promoter binds a number of tissue-specific and ubiquitous transcription factors. Of these, the homoeodomain protein PDX-1 (pancreatic duodenal homeobox factor-1), the basic leucine zipper protein MafA and the basic helix-loop-helix heterodimer E47/BETA2 (beta-cell E box transactivator 2; referred to here as beta2) bind to important regulatory sites. Previous studies have shown that PDX-1 can interact synergistically with E47 and beta2 to activate the rat insulin 1 promoter. The aim of the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 49 publications
4
69
1
Order By: Relevance
“…There was no change in total insulin content or output in INS-1E cells. Pdx1 and MafA are potent stimulators of the transcription of insulin genes (Docherty et al 2005), and the increased Pdx1 mRNA expression found in this study ( Fig. 2A) is very interesting; it is in accordance with increased mRNA expression of Pdx1 in isolated islets from T2D patients, despite less insulin release than control islets in response to glucose (Del Guerra et al 2005); furthermore, it has previously been shown that glutamine upregulates Pdx1 expression in BRIN-BD11 cells (Corless et al 2006).…”
Section: Discussionsupporting
confidence: 72%
“…There was no change in total insulin content or output in INS-1E cells. Pdx1 and MafA are potent stimulators of the transcription of insulin genes (Docherty et al 2005), and the increased Pdx1 mRNA expression found in this study ( Fig. 2A) is very interesting; it is in accordance with increased mRNA expression of Pdx1 in isolated islets from T2D patients, despite less insulin release than control islets in response to glucose (Del Guerra et al 2005); furthermore, it has previously been shown that glutamine upregulates Pdx1 expression in BRIN-BD11 cells (Corless et al 2006).…”
Section: Discussionsupporting
confidence: 72%
“…42 In physical contiguity with PCGEM1 is located the gene Neuro D1, whose ectopic expression causes conversion of epithelial cells into neurons 43 and is actively expressed in advanced prostate cancer. 30 Neuro D1 is further able to interact with the insulin promoter 44 and is between major players of pancreas organogenesis as is expressed in all differentiated and postmitotic pancreatic endocrine cells. It has been postulated that the involvement of Neuro D1 in promoting cell cycle exit inducing pancreatic progenitor cells to differentiate.…”
Section: Discussionmentioning
confidence: 99%
“…These interacting factors include bHLH proteins that bind to Eboxes (BETA2/NeuroD1 and E2A proteins) [122,123,140,141], the basic leucine zipper factor MafA that binds to the C-box [73,142], the homeodomain proteins Pbx1 and MEIS2 [47,48,143,144], and high mobility group (HMG) proteins that bind to the DNA backbone [123]. The free energy gained from these interactions may increase the likelihood that Pdx1 targets genes with binding sites for these factors [123,144].…”
Section: Mechanisms Of Transcriptional Regulation By Pdx1mentioning
confidence: 99%